Educational Competencies And Training Requirements Of The Pro-school Childs Educators Annaba - Kemach, Amel; Boumengar, Mourad (Journal of Human Sciences, 2022)
The study aimed to identify the educational competencies and training requirements of the pro-school child s educators based on their perspective , and taking into account the change of the academic qualifications and previous experiences in the primary school . The study required to choose (15) pro-school child s educators that works at the preparatory education department , and the researche prepared a survey instrument for the study in which it consisted (40) competence divided on four educational competencies and training requirements field to assess the practice of the pro-school child s educators to these qualities.